Voter Support for Privatizing Education: Evidence on Self-Interest and Ideology - Wolfram Merzyn; Heinrich Ursprung (Center for Economic Studies and ifo Institute (CESifo), 2003)
Economic theory advances various arguments in favor of and against privatizing education. In this paper we investigate the extent to which these arguments influence voters' opinions. We analyze two popular referenda in which some 400,000 voters in two Swiss cantons expressed their opinions on the issue of education vouchers and direct subsidies to private schools. We find that successful attempts to move towards a more privatized education system rest mainly on pure income effects, some other socio-economic determinants, ideological convictions, and possibly the perceived quality of the public schools. Peer-group and tax-burden effects, which play a prominent role in the theoretical literature, do not appear to significantly influence voting behavior.
Keywords: 330; political economy; voter behavior; privatization; education policy; vouchers